2012
DOI: 10.1242/dev.079491
|View full text |Cite
|
Sign up to set email alerts
|

AIP1 acts with cofilin to control actin dynamics during epithelial morphogenesis

Abstract: SUMMARYDuring epithelial morphogenesis, cells not only maintain tight adhesion for epithelial integrity but also allow dynamic intercellular movement to take place within cell sheets. How these seemingly opposing processes are coordinated is not well understood. Here, we report that the actin disassembly factors AIP1 and cofilin are required for remodeling of adherens junctions (AJs) during ommatidial precluster formation in Drosophila eye epithelium, a highly stereotyped cell rearrangement process which we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 32 publications
5
39
0
Order By: Relevance
“…For instance, in epithelial cells neural Wiskott-Aldrich Syndrome Protein (N-WASP) works with WIRE to stabilize F-actin, though the mechanism is not yet understood [45]. Conversely, the actin severing proteins AIP1 and cofilin are needed for destabilization and remodeling of AJ [46].…”
Section: Force Transmission Modulementioning
confidence: 99%
“…For instance, in epithelial cells neural Wiskott-Aldrich Syndrome Protein (N-WASP) works with WIRE to stabilize F-actin, though the mechanism is not yet understood [45]. Conversely, the actin severing proteins AIP1 and cofilin are needed for destabilization and remodeling of AJ [46].…”
Section: Force Transmission Modulementioning
confidence: 99%
“…Ovaries were dissected and cultured in Schneider's medium cocktail as described previously for use of live imaging (Chu et al, 2012;Prasad and Montell, 2007). After dissection, egg chambers were incubated in Latrunculin A (2 μM in Schneider's medium cocktail, Invitrogen) for 1 hour before fixation, and were then stained as described above.…”
Section: Latrunculin a Treatmentmentioning
confidence: 99%
“…This protein promotes rapid actin turnover by interacting with cofilin-decorated actin filaments and enhancing their disassembly [3134]. In Drosophila , inactivation of the Aip1 homolog Flare causes defects similar to cofilin ( Twinstar ) mutants, including accumulation of excess F-actin and increased stability of actin networks [35, 36]. Our experiments revealed that Aip1 silencing caused F-actin accumulation and moderate border cell migration delays as detected from fixed stage 10 egg chambers.…”
Section: Resultsmentioning
confidence: 73%